2007
DOI: 10.1111/j.1742-1241.2007.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum gastrin concentration and changes in G and D cell densities in gastric antrum in children with chronic gastritis

Abstract: The mean G/D cell ratios in groups I and III were almost identical. The mean fasting serum gastrin concentration was higher in children with both chronic gastritis and H. pylori infection compared with patients without infection or without antral inflammation. No difference in the G cell density or D cell density in children was found, regardless of the presence or absence of gastritis or H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
3
6
1
Order By: Relevance
“…found that the mean fasting serum gastrin level was higher in children with H. pylori ‐associated gastritis compared to H. pylori ‐negative cases, with or without gastritis. In contrast to earlier studies suggesting that a decrease in the number of somatostatin‐producing D cells with an unchanged number of gastrin‐producing G cells may lead to PUD, these authors found no difference in G‐cell density and D‐cell density, regardless of the presence or absence of gastritis or H. pylori infection [7].…”
Section: Pathogenesiscontrasting
confidence: 88%
“…found that the mean fasting serum gastrin level was higher in children with H. pylori ‐associated gastritis compared to H. pylori ‐negative cases, with or without gastritis. In contrast to earlier studies suggesting that a decrease in the number of somatostatin‐producing D cells with an unchanged number of gastrin‐producing G cells may lead to PUD, these authors found no difference in G‐cell density and D‐cell density, regardless of the presence or absence of gastritis or H. pylori infection [7].…”
Section: Pathogenesiscontrasting
confidence: 88%
“…It is also speculated that a decrease in somatostatin secretion, one of the factors inhibiting acid secretion, is the main cause of hyperacidity in H. pylori infection. A comparison of the G/D cell ratio between our study and that by Czaja et al [4] showed no increase in G cells but a decrease in D cells resulting in a high G/D ratio in our patient. Thus, a decrease in somatostatin secretion due to a reduction in D cell population might have induced hypergastrinemia in this case.…”
Section: Discussionsupporting
confidence: 61%
“…The specimen from the control patient showed 76 G cells, 62 D cells, and a G/D cell ratio of 1.22. In the Czaja report, the mean G cell count was 79, D cell count 45, and G/D cell ratio 1.79 in the normal controls [4]. The immunostaining study showed that the D cell count in this patient was lower than in controls, resulting in an increased G/D ratio.…”
Section: Case Reportmentioning
confidence: 78%
See 1 more Smart Citation
“…The details are presented in table 1. Also the changes in the number of D and G cells in atrophic gastritis were observed and several studies presented the therapy promoting the secretion of gastric acid and gastric pepsin and regulating the neuroendocrine mechanism in rats (Zhu et al, 2008;Wang et al, 2009;Czaja et al, 2008;Todorovic et al, 2008). However, as it was reported (Czaja et al, 2008), changes of serum gastrin concentration in gastric antrum in children with chronic gastritis are not statistically significantly connected with D and G cell densities.…”
Section: Diagnostic Influence Of Neuroendocrine Cell Morphometrymentioning
confidence: 51%